Analysis of Tobacco Cessation Programs in Dental Settings - Niharika Benjamin; Varsha Choubey; Meenakshi Bhasin; Bedkekar Sushma; Anushree Choudhary; Pallavi Ammu Thomas (Journal of Pharmacy and Bioallied Sciences)
Background: Tobacco use is a leading cause of preventable diseases, including oral cancer and periodontal disease. Dental settings offer a unique opportunity for tobacco cessation interventions due to the frequent patient–dentist interactions. Materials and Methods: A randomized controlled trial was conducted across 20 dental clinics. Participants included 400 adult tobacco users who were randomly assigned to either an intervention group (n = 200) or a control group (n = 200). The intervention group received a comprehensive tobacco cessation program consisting of behavioral counseling, nicotine replacement therapy, and follow-up sessions over 6 months. The control group received standard care, which included general advice on quitting tobacco. Data on tobacco use, quit rates, and oral health status were collected at baseline, 3 months, and 6 months. Statistical analysis was performed using SPSS 24.0, and significance was set at P < 0.05. Results: At 6 months, the intervention group showed a significantly higher quit rate (45%) compared to the control group (20%) (P < 0.001). Additionally, participants in the intervention group exhibited significant improvements in oral health parameters, including reductions in periodontal pocket depths (a mean reduction of 2.5 mm) and improvements in gingival health scores. Satisfaction with the program was high among participants in the intervention group, with 85% reporting they would recommend the program to others. Conclusion: The tobacco cessation program implemented in dental settings significantly increased quit rates and improved oral health outcomes compared to standard care. These findings suggest that integrating tobacco cessation programs into routine dental practice can effectively reduce tobacco use and enhance oral health.